Study of carbonated soft drink consumption among selected primary school children in Malaysia / Phua En Kiat - Phua , En Kiat (2017)

(untitled)
According to a report by Euromonitor International in 2014, total sales volume of all soft drinks increased by 11% from 1574.2 million litre in 2011 to 11748.3 million litre in 2013. In 2012, World Health Organization (WHO) reported that 23.2% of Malaysian children and adolescents consumed soft drinks once or more than once per day. Several studies have provided scientific evidence on the association between soft drink consumption and increased risk of health issues such as obesity, chronic disease and others. The main purpose of this research is to identify the pattern of soft drink consumption among primary school children in selected areas, and to determine the factors influencing children’s soft drink intake based on the Theory of Planned Behaviour (TPB). In this study, survey was conducted as the research methodology and a total of 454 respondents were recruited from urban areas (Petaling Jaya and Cheras, Selangor) and rural areas (Parit Ya’ani, Yong Peng and Batu Pahat, Johor) of Malaysia. The results showed that about 94.9% of respondents consume soft drinks at least once a week and only 5.1% of respondents reported that they rarely consume soft drinks. About 27.5% of respondents reflected that they consume soft drinks more than 500 ml per day. Results also showed that 47% consumed soft drinks at home, followed by 30% who had it in school. The results showed that there was no significant difference between amount of daily soft drink consumption and age (p=0.942), living area (p=0.063), but there was significant difference between gender (p=0.001), ethnic group (p=0.018) and family income (p<0.001). Multiple linear regression has been used to analyse the data and find out the factors influencing soft drink intake behaviour among the school children. The results showed that intention to consume soft drinks (t=16.18, p< 0.001) was significantly influencing the soft drink intake but perceived behavioural control was not (t= 0.183, p=0.854). Attitude towards the soft drink consumption (t=8.916, p<0.001), subjective norm (t=5.924, p<0.001) and perceived behavioural control (t=2.272, p<0.001) had significant influence on the intention. Being healthy (β=0.114; t=2.479, p<0.05)), family members (R²=0.026, p<0.05) and soft drink availability at home (R²=0.539; β=0.109; t=10.884, p<0.0001) had the most significant effects on attitude towards soft drink consumption, subjective norm and perceived behavioural control respectively. This study provides a valuable insight into children’s soft drinks consumption behaviour in selected areas and identifies the factors that influence it. A better planning and implementing nutrition intervention should be developed based on this finding to improve the health of Malaysian children.